Policing Gender, Class And Family In Britain, 1800-1945 - Mahood, Linda (Taylor & Francis, 1995)
This book is intended for undergraduate courses on modern British history, women's history, courses on family, sexuality and childhood. Women's studies, history of education, sociology.
English
Keywords: Sociology; Crime & criminology; industrial; schools; national; vigilance; association; day; residential; school; magdalene; asylum